Green synthesis of metal-based nanoparticles for sustainable agriculture. (15th September 2022) - Jiang, Yaqi; Zhou, Pingfan; Zhang, Peng; Adeel, Muhammad; Shakoor, Noman; Li, Yuanbo; Li, Mingshu; Guo, Manlin; Zhao, Weichen; Lou, Benzhen; Wang, Lingqing; Lynch, Iseult; et al.
Abstract: The large-scale use of conventional pesticides and fertilizers has put tremendous pressure on agriculture and the environment. In recent years, nanoparticles (NPs) have become the focus of many fields due to their cost-effectiveness, environmental friendliness and high performance, especially in sustainable agriculture. Traditional NPs manufacturing methods are energy-intensive and harmful to environment. In contrast, synthesizing metal-based NPs using plants is similar to chemical synthesis, except the biological extracts replace the chemical reducing agent. This not only greatly reduces the used of traditional chemicals, but also produces NPs that are more economical, efficient, less toxic, and less polluting. Therefore, green synthesized metal nanoparticles (GS-MNPs) are widely used in agriculture to improve yields and quality. This review provides a comprehensive and detailed discussion of GS-MNPs for agriculture, highlights the importance of green synthesis, compares the performance of conventional NPs with GS-MNPs, and highlights the advantages of GS-MNPs in agriculture. The wide applications of these GS-MNPs in agriculture, including plant growth promotion, plant disease control, and heavy metal stress mitigation under various exposure pathways, are summarized. Finally, the shortcomings and prospects of GS-MNPs in agricultural applications are highlighted to provide guidance to nanotechnology for sustainable agriculture.